Pelayanan Publik Program E-Samsat Di Kantor Samsat Kota Gororntalo - Rizcha Mayanti Paera; Rosman Ilato; Zuchri Abdussamad (Gorontalo State University, 2022)
ABSTRACT This study aims to determine (1) the principles of public service for the E-samsat program in Gorontalo City. (2) The determinants of public services for the E-samsat program at the Gorontalo City Samsat office are viewed from the aspects of communication, human resources, disposition, and bureaucracy. This research method uses qualitative research methods with descriptive type using data analysis techniques from collecting, reducing, presenting data, and drawing conclusions. Based on the results of research which were analyzed in the field that (1) Judging from the principles of service, this program has not been able to improve services at the SAMSAT office because of several problems in the system and public knowledge is still minimal in the use of E-samsat. (2) judging from the determinants of public services, the E-samsat program at the Gorontalo City SAMSAT office has started to run well, it just needs some improvements in terms of resources so that the program can run well.